Convolutional neural network model for early detection of meatballs containing borax - Aryo Michael; Juprianus Rusman (Institute of Computer Science (IOCS), 2023)
The use of borax in meatballs to improve the texture and durability of meatballs is still rampant. Borax is very dangerous for consumers. Currently, monitoring of meatballs containing borax is done by experts in the laboratory. The public needs to know this information quickly. Therefore, a system is needed that can detect meatballs containing borax in real time. In this study we built a lightweight Convolutional Neutal Network (CNN) model and searched for optimal hyperparameters for the classification of meatballs containing borax. The results show that the proposed model outperforms other models in classifying meatballs containing borax with an accuracy value of 90%.